The Impacts of Climate Change and Adaptation Measures for Rice Production in Central Vietnam: A Pilot in Nui Thanh District, Quang Nam Province - Trang, Bui Thi Thu; Hanh, Nguyen Thi Hong (VNU Journal of Science: Earth and Environmental Sciences, 2017)
This study analyses the impacts of climate change on rice production and adaptation in Nui Thanh district, Quang Nam province. This study pursues to seek following queries including forecast future rainfall, temperature, rice yield, and analyze adaptation measures to improve rice production under different climate change scenarios in Nui Thanh district, Quang Nam province, Vietnam. The study was based on firstly identification of the problem in the study area followed by collection of secondary data on weather, soil characteristics and crop management. Then the downscaling model was used to predict the temperature and precipitation of the study area in the future by A2 and B2 scenarios. The Aquacrop model was used to simulate the yield response. After that, the impact of climate change scenarios on rice yield was analyzed. Lastly, the evaluation for adaptation measure to improve rice production under climate change based on water management was determined. Results show that climate change will reduce rice yield from 1.29 to 23.05% during the winter season for both scenarios and all time periods, whereas an increase in yield by 2.07 to 6.66% is expected in the summer season for the 2020s and 2050s; relative to baseline yield. The overall decrease of rice yield in the winter season can be offset, and rice yield in the summer season can be enhanced to potential levels by altering the transplanting dates and by introducing supplementary irrigation. Late transplanting of rice shows an increase of yield by 20- 27% in future. Whereas supplementary irrigation of rice in the winter season shows an increase in yield of up to 42% in future. Increasing the fertilizer application rate enhances the yield from 0.3 to 29.8% under future climates. Similarly, changing the number of doses of fertilizer application increased rice yield by 1.8 to 5.1%, relative to the current practice of single dose application. Shifting to other heat tolerant varieties also increased the rice production. Keywords Adaptation measure, Aquacrop model, climate change, climate change scenarios, SDSM model References [1] Chinvanno, S.,2010. Climate change adaptation as a development strategy: Amajor challenge for Southest Asian Countries. Southeast Asia START Regional Center, Chulalongkon University, Thailand. [2] Geerts, S., Raes, G., and Garcia, M., 2010. Using Aquacrop to derive deficit irrigation schedules. Agricultural Water Management. [3] Parry, M. L., Rosenzweig, C., Iglesias, A., Livermore, M., Fischer, G., 2004. Effects of climate change on global food production under SRES emissions and socio-economic scenarios. Global Environmental Change 14 (2004) 53–67. [4] Reidsma, P., Ewert, F., Lansink, A. O., Leemans, R., 2010. Adaptation to climate change and climate variability in European agriculture: The importance of farm level responses, European Journal of Agronomy, 32: 91-102. [5] Tao, F., Zhao, Z., 2010. Adaptation of maize production to climate change in North China Plain: Quantify the relative contributions of adaptation options. European Journal of Agronomy, 33: 103-116. [6] Thuc, Tran., 2010. Impacts of climate change on water resources in the Huong River basin and adaptation measures. VNU Journal of Science, Earth Sciences 26 (2010), pp. 210-217. [7] Tran Duc Vien., 2011. Climate change and its impacts on agriculture in Vietnam. J. ISSAAS Vol.17, No.1/17-21 (2011).